Atheism in the medieval Islamic and European world: the influence of Persian and Arabic ideas of doubt and skepticism on medieval European literary thought - Azinfar, Fatemeh Chehregosha (Ibex Publ., 2008)
Acknowledgements -- Introduction -- The question of 'orientalism' in the medieval texts -- A thousand and one nights revisited -- Shaharazad's moral world : a feminist case of recreation and unity -- Dissent, skepticism and medieval texts : La Chanson de Roland and its Persian prototype Vis and Ramin -- Abelardian logic : working out the principles of rationality in Dante's the Divine comedy -- A lover's game : redefining the laws of Christianity in the Pearl poem -- Usurping the voice of authority : Chaucer's reply